ANALISIS RASIO KEUANGAN PADA KOPERASI MADU KELULUT “KUKAR IDAMAN LESTARI” DI KELURAHAN MANGKURAWANG TENGGARONG - Palinggi, Yonathan; Erwinsyah, Erwinsyah; Akbar, Ali; S, Syahruddin; Ilham, Ilham; Juanda, Rendy; Hermanto, M.; Amir, Kartika Sari (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2024)
This research was conducted to determine and examine the financial performance of a Cooperative. This research was conducted at the Kelulut Honey Cooperative "Kukar Idaman Lestari" using quantitative descriptive research methods. The data used in this study come from the financial statements of the Kelulut Honey Cooperative "Kukar Idaman Lestari" in the form of Balance Sheet Financial Statements and Income Statements between 2021 and 2023. The data analysis technique in this study uses quantitative analysis, namely, analyzing financial statements with a financial ratio approach in the form of liquidity, solvency, profitability and activity. Based on the results of the discussion of the financial performance analysis above, it can be concluded that the overall hypothesis about the proposed Cooperative's financial performance is rejected or not proven correct. In the hypothesis proposed that the financial ratios in the Kukar Idaman Lestari Honey Kelulut Cooperative have decreased from the previous year both in terms of Solvency which has decreased, in terms of Activity which is moving slowly and Profitability which has decreased.